Activation Level and Probabilities of Electromagnetic γ-transitions in the Reaction 77Se(γ,γ’)77mSe - Viktor Zhaba; Eduard Gohman (Ital Publication, 2020)
The dependence of the absolute yield from energies for reaction (γ,γ’)m on the nucleus 77Se was approximated by fit dependences (lines). Due to the visually detected fracture of the reaction yield, the energy interval 5.75-8.0 MeV is conventionally divided into two parts. For the transition step as one experimental point, the left part was approximated to 6.6 MeV, and the right part - from 6.26 MeV. There approximations were eight for both intervals. Given the features of the calculation and the minimum values for χ2, the